The anti-dumping policy of the European Communities - Rolf Weidemann (Intereconomics, 1990)
In the recent discussion of EC anti-dumping rules and their application allegations have intensified that this instrument, provided by the GATT to counteract unfair trade practices, has increasingly been used by the Community to raise new trade barriers reflecting the amplification of protectionist intentions and resulting as a matter of fact in a restriction of imports contrary to the provisions and the scope of GATT. Is this a realistic assessment?
Keywords: 330; Protectionism